Analysis of Basic Shooting Skills in Soccer Among Extracurricular Participants at SMA Muhammadiyah Klaten - Aldi Danu Prakasa; Gatot Jariono; Nurhidayat Nurhidayat; Sudirman Burhanuddin (Ilmu Olahraga, 2026)
This study aims to identify and describe the level of basic shooting technique skills among students participating in the football extracurricular activity at SMA Muhammadiyah Klaten. The study employed a quantitative descriptive approach to provide an objective description of students' shooting abilities based on numerical data obtained through field testing. The research was conducted at SMA Muhammadiyah Klaten, Central Java, involving all 34 students participating in the football extracurricular activity using a total sampling technique. Data collection was carried out using a football shooting test instrument adapted from Sepdanius et al (2019), by providing three opportunities to perform a shot from a distance of 16.5 meters toward predetermined target areas on the goal. The assessment was conducted based on the aspects of target accuracy, movement execution, ball control, and technique consistency. The data were analyzed using quantitative descriptive statistics with the assistance of IBM SPSS Statistics to obtain frequency distributions and percentages. The results showed that the level of students' basic shooting technique skills was generally in the moderate category. Of the 34 students who participated in the test, 3 students (8.82%) were classified in the very good category, 11 students (32.36%) in the good category, 15 students (44.12%) in the moderate category, 5 students (14.70%) in the poor category, and no students were classified in the very poor category. These findings indicate that the football extracurricular training program has made a positive contribution to the development of students' shooting abilities, particularly in the aspects of accuracy, movement coordination, and shooting control. Therefore, continuous and structured training is required to further improve students' shooting skills so that they can support the achievement of more optimal football performance.